"Calcium receptors" on eukaryotic cells with special reference to the osteoclast. Issue 6 (December 1990) - Zaidi, Mone
Abstract : There is a growing list of cells that are capable of detecting and responding to changes in the concentration of extracellular calcium. The two classic examples of this behaviour are the calcitonin-secreting parafollicular cells of the thyroid and parathyroid hormone-secreting chief cells of the parathyroid gland. A more recent addition to this list is the renin-secreting juxtaglomerular cell of the kidney. Particularly intriguing has been independently the discovery by two laboratories, that the resorptive cell of bone, the osteoclast, is capable of detecting changes in ambient calcium. A common theme amongst all these so called "calcium-responsive" cells is that extracellular calcium increases elevate intracellular calcium levels, and this intracellular signal is either stimulatory or inhibitory to the functional response. But how these cells detect changes in the concentration of extracellular calcium, and how these recognition events are subsequently transformed into intracellular signals that regulate cell function are somewhat less clear. The commentary reveals some recent developments that seemingly provide insights into these mechanisms, with special reference to the osteoclast.